From Bureaucracy to Bullets : Extreme Domicide and the Right to Home - Akesson, Bree (Genocide, Political Violence, Human Rights Ser., 2022)
As of 2019, there were over 70 million people displaced from their homes, the most displaced persons since the Second World War. This number continues to rise as solutions to stem large-scale violence and subsequent displacement continue to fail. Today, twenty-four people are displaced from their homes and communities every minute. The likelihood of the displaced returning to their homes is become increasingly unlikely as their homes may have been destroyed as a result of conflict and war. What are the impacts of loss of home upon children, adults, families, communities, and societies? If having a home is a basic human right, then why is the destruction of one's home not viewed as a violation of human rights and prosecuted accordingly? This book answers these questions and more by focusing on domicide, or the intentional destruction of the home, as a human rights issue.